(untitled) (Raparin Journal of Humanities (RJH), 2025)
This research conducts a semiotic analysis of icons in poet Abdulsattar Noor Ali’s work, examining their cultural meanings and functions within his poetry using analytical semiotic methodology. Key Focus Areas The study categorizes semiotic icons into four main groups: Historical Icons - References to notable historical figures (writers, poets, political leaders) and significant past events, showing the poet’s engagement with historical heritage. Religious Icons - Allusions to Quranic verses, religious figures, and both Islamic and non-Islamic rituals. Political and National Icons - Symbols representing political issues, conflicts, patriotism, national identity, and expressions of homeland suffering. Artistic and Aesthetic Icons - References to artistic concepts (music, visual arts), natural beauty (mountains, rivers, birds, forests), and themes of love and emotion. Research Objectives 1.Analyze the poet’s effective deployment of icons within his texts 2.Examine the innovative connection between signifier (icon) and signified (meaning) 3.Uncover layered meanings embedded within these icons 4.Study how icons interact with cultural, social, historical, and religious contexts to create new meanings that influence and persuade audiences Methodology The study employs analytical semiotic methodology to investigate icons and their varied cultural significance as expressed in the poet’s work, while exploring how these elements engage and capture audience attention.